Antidiabetic Treatment with Gliptins Focus on Cardiovascular Effects and Outcomes - Reham Nasser Alosaimi; Nourah Hassan Alzahraani; Anwar Ali Wali Haddadi; Saleh Abdullah Alzahraani; Abdulmajeed Hussam Saeedi; Sultan Sa’ad Al Mutairi; Ftoon Adnan Bafail; Neamah Nashi Ibrahim Almahwary; Mohammed Jaber Alshamrani; Saif Khaled Mesfer Almalki; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: The occurrence of cardiovascular disease(CVD) and type 2 diabetes mellitus(T2D) is experiencing a significant increase as a result of the worldwide problem of overweight and obesity. Aim: The objective of this systematic review and meta-analysis was to assess the effects and results of gliptins on cardiovascular system of diabetic rats. Materials and methods: This systematic review has been done in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses(PRISMA) statement and the criteria outlined in the Cochrane Handbook for systematic reviews of interventions. The Cochrane Risk of Bias Assessment Tool 1(ROB 1) has been utilized to evaluate the quality of the trial. Main finding: As regard systolic Blood Pressure of studied population, our meta-analysis resulted in pooled MCs and corresponding 95% CI of ;137.1(133.9, 140.3), major heterogeneity was detected among our pooled studies with I2 and chi-p= 100%and <0.001, As regard prior CVD, our meta-analysis resulted in pooled RR and the corresponding 95% CI ; 0.7(0.5, 0.9), major heterogeneity was detected among our pooled studies with I2 and chi-p= 100%and <0.001, Figure 5; illustrated forest plot for this outcome. Heart failure was reported in five studies, our pooled meta-analysis resulted in pooled RR and corresponding 95% CI; 0.18(0.1, 0.25), major heterogeneity was detected among our pooled studies with I2 and chi-p= 100%and <0.001, Conclusion: Gliptins or DPP-4 inhibitors provide effective glycemic control with good tolerability, particularly without severe hypoglycemia, and also offer non-glycemic benefits on CV risk factors in T2DM patients.